Pembangunan Sistem Informasi Akademik Lembaga Bimbingan Belajar Spectrum - Wardani, Kristin Tyas (Speed - Sentra Penelitian Engineering dan Edukasi, 2012)
Abstrac: Education is the most important infrastructure, especially in the development of individual potential, and generally in the development potential of the nation. To that end, efforts to develop the quality of education is an absolute must to get attention. With the development of educational technology, it is expected a significant increase in the education sector, both in local and national scale. Improving the quality of education can include improving the quality of teaching materials, student understanding, as well as the competence of the teachers (Ruly Darmawan, 2006). One tutoring place that is still in great demand today is Pacitan Tutoring Spectrum Institute. This is evident with the increasing number of students from year to year. Learning spaces are comfortable, professional educators as well as the low cost of learning is one of the reasons Spectrum Tutoring Agency is currently in great demand. Currently Spectrum Tutoring Agency is still using a conventional manner in the processing of data, student data, data of teachers, students and the value of payments. Like, when there are students registering must fill out a registration form after the officers had to move it in the books, so it takes a long time. In addition to the students who will pay to wait too long because the officer should seek student data one by one in the books. Officers are also difficulties in making a report to the leadership (Spectrum, 2008). The main purpose of this penelitin is making the information systems that can be used for data collection at the Institute for Academic Tutoring Spectrum. The method taken by the authors observe, interview, library study, analysis, information system design followed by construction of information systems and the next is a trial. The results of this study is to provide facilities in the academic data processing, such as student data, payment data, data of teachers, and to simplify the search process other than the data storage medium that has a more effective and larger. Keywords: Information Systems Institute for Academic Tutoring Spectrum   Abstrak : Pendidikan merupakan infrastuktur yang terpenting khususnya dalam pengembangan potensi individu, dan umumnya dalam pengembangan potensi bangsa. Untuk itu, upaya pengembangan kualitas pendidikan merupakan hal yang mutlak untuk mendapatkan perhatian. Dengan dikembangkannya teknologi pendidikan, diharapkan adanya peningkatan yang signifikan dalam sektor pendidikan, baik dalam skala lokal maupun nasional. Peningkatan kualitas pendidikan ini dapat meliputi peningkatan kualitas materi ajar, pemahaman siswa, sekaligus kompetensi para pengajarnya (Ruly Darmawan, 2006). Salah satu tempat bimbingan belajar yang masih banyak diminati di Pacitan saat ini  adalah Lembaga Bimbingan Belajar Spectrum. Hal ini terbukti dengan semakin bertambahnya jumlah siswa dari tahun ke tahun. Ruang belajar yang nyaman, tenaga pendidik yang profesional serta biaya belajar yang murah merupakan salah satu alasan Lembaga Bimbingan Belajar Spectrum saat ini banyak diminati. Saat ini Lembaga Bimbingan Belajar Spectrum masih menggunakan cara yang konvensional dalam pengolahan data, baik data siswa, data guru, pembayaran maupun nilai siswa. Seperti, ketika ada siswa mendaftar harus mengisi formulir pendaftaran setelah itu petugas harus memindahkannya dalam pembukuan, sehingga dibutuhkan waktu yang cukup lama. Selain hal tersebut siswa yang akan membayar pun harus menunggu lama karena petugas harus mencari satu persatu data siswa dalam pembukuan. Petugas juga kesulitan dalam membuat laporan kepada pimpinan (Spectrum, 2008).    Tujuan utama dari penelitin ini adalah pembuatan sistem informasi yang dapat digunakan untuk pendataan akademik di Lembaga Bimbingan Belajar Spectrum. Metode yang diambil penulis yaitu dengan melakukan observasi, wawancara, study pustaka, analisis, perancangan sistem informasi dilanjutkan dengan pembangunan sistem informasi dan selanjutnya adalah uji coba. Hasil dari penelitian ini adalah untuk memberikan kemudahan dalam proses pengolahan data akademik, seperti data siswa, data pembayaran, data guru, dan untuk mempermudah dalam proses pencarian data selain itu memiliki media penyimpanan yang lebih efektif dan lebih besar. Kata Kunci : Sistem Informasi  Akademik Lembaga Bimbingan Belajar Spectrum